Ratios in Proportion: What Should the Shape of the Package Be? - Raghubir, Priya; Greenleaf, Eric A. (Journal of Marketing, 2006)
Consumers’ reactions to rectangles have implications for package and product design. In two lab studies and an analysis of field data, the authors find that the ratio of the sides of a rectangular product or package can influence purchase intentions and preferences and is related to marketplace demand. In more exploratory inquiries, the authors also find that the impact of this ratio on consumers depends on the relative seriousness of the context in which the product is used. Furthermore, ratio can also affect product perceptions, and consumers appear to prefer a range of contiguous ratios for different contexts rather than a particular ratio.